2018
DOI: 10.3389/fgene.2018.00410
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association and Mechanistic Studies Indicate That Immune Response Contributes to Alzheimer’s Disease Development

Abstract: Alzheimer’s disease (AD) is the most common cause of dementia. Although genome-wide association study (GWAS) have reported hundreds of single-nucleotide polymorphisms (SNPs) and genes linked to AD, the mechanisms about how these SNPs modulate the development of AD remain largely unknown. In this study, we performed GWAS for three traits in cerebrospinal fluid (CSF) and one clinical trait in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort. Our analysis identified five most significant AD related S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Prolonged activation of glial cells, microglia and astrocytes in particular, and the release of proinflammatory cytokines, chemokines, and reactive oxygen and nitrogen species, create a neurotoxic environment which could exacerbate the progression of AD (9)(10)(11). Recent genome wide association studies have identified multiple immune related gene variants as risk factors for late-onset AD, supporting a major contributing role of innate immunity and neuroinflammation in AD (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged activation of glial cells, microglia and astrocytes in particular, and the release of proinflammatory cytokines, chemokines, and reactive oxygen and nitrogen species, create a neurotoxic environment which could exacerbate the progression of AD (9)(10)(11). Recent genome wide association studies have identified multiple immune related gene variants as risk factors for late-onset AD, supporting a major contributing role of innate immunity and neuroinflammation in AD (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that 19q13.32 is a risk locus of Alzheimer's disease and rs429358 is one of the two variants in the APOE ε4 locus. In this region, we tagged variants associated with dementia and decline in mental ability, including Alzheimer's disease [57][58][59] , frontotemporal dementia 60 , cerebral amyloid angiopathy 61 , cognitive decline 62 , cognitive impairment test score 63 , as well as many biomarkers of Alzheimer's disease, such as neurofibrillary tangles 61 , neuritic plaque 61 , cerebral amyloid deposition 64 , cerebrospinal fluid protein levels 63 , and cortical amyloid beta load 65 . Altered amplitude activity has been widely reported in patients of cognitive impairment and Alzheimer's disease 66,67 .…”
Section: The Shared Genetic Loci With Brain-related Complex Traits Anmentioning
confidence: 99%
“…Genetic analysis of late‐onset AD has uncovered a number of single nucleotide polymorphisms (SNPs) that are associated with the risk for AD, including KIR2DS2/KIR2DL2/HLA‐C1, apolipoprotein E (APOE), phosphatidylinositol binding clathrin assembly protein (PICALM), complement receptor 1 (CR1) and clusterin (CLU), glycoprotein carcinoembryonic antigen‐related cell adhesion molecule‐16, B‐cell lymphoma‐3, translocase of outer mitochondrial membrane 40 homolog (TOMM‐40), apolipoprotein C‐I (APOC1), and C‐type lectin domain A family‐16 member, paired immunoglobulin‐like type 2 receptor (PILRα), nectin‐2 (also known as poliovirus receptor‐related 2, PVRL‐2) . Nectin‐2, TOMM‐40, APOE, and APOC1 are closely located in chromosome 19.…”
Section: Susceptible Genetic Factors Of Ad Facilitate Herpesviral Infmentioning
confidence: 99%
“…Nectin‐2, a member of the (Ig) superfamily, is expressed in a variety of cell tissues including neurons. It serves as a glycoprotein D receptor and is required for viral entry and spreading of HSV‐1 . Cholesterol 25‐hydroxylase (CH25H) gene is also identified as an AD susceptibility gene, which is highly expressed in specifically vulnerable brain regions of AD patients.…”
Section: Susceptible Genetic Factors Of Ad Facilitate Herpesviral Infmentioning
confidence: 99%